Identification of current best practices for short-term medical mission trips and adherence to current common principles and guidelines - Susan Andrews (Health for All Nations, 2020)
Background: Recent reviews of published guidelines for conducting short-term medical missions (STMM) identify significant concerns about the lack of adherence and of formal regulations concurrent with the increasing number of individuals and organizations participating in STMM. Method: A descriptive survey methodology was used. A 44-item survey that identifies current practices utilized by healthcare providers (HCP) who have participated in STMM was used based on the literature and prior research, and distributed electronically to HCP participating in STMM to identify current best practices and compare findings with the most recent recommendations for short-term global health activities. A focus on current operational practices was surveyed and analyzed to develop operational recommendations for the ethical and safe care provided during STMM. Results: Eighty-seven surveys were included in the final analysis with 33% (N=29) serving as coordinators for the trip. The majority of the respondents were female (67%), and the primary roles represented were: MD (N=17; 20%), nurse practitioner (N=20; 23%), and registered nurse (N=18; 21%). A majority (N=48; 67%) traveled to South America or Latin America with 38% (N=33) having participated in four or more STMM. Language proficiency was reported as deficient (N=35; 40%) along with little or no knowledge of the basic culture (N=39; 45%). Additional data were collected on trip preparation, clinic operations, and outcomes follow up. Conclusions: Using a convenience sample, the results of the survey provide information on the current practices utilized by HCP who have participated in STMM and compare the findings to assess for adherence with the most recent recommendations for short-term global health activities. There was variation in the degree to which HCPs were knowledgeable about specific aspects related to knowledge of local culture, language proficiency, and adherence to recommended practices for STMM. Additional research on STMM is needed, along with further exploration of how evidence-based practices for STMM can be implemented to improve access and safety to the care provided while in the host country.